Anti-inflammatory effect of active nanofibrous polymeric membrane bearing nanocontainers of atorvastatin complexes. (December 2017) - Schwinté, Pascale; Mariotte, Alexandre; Anand, Priya; Keller, Laetitia; Idoux-Gillet, Ysia; Huck, Olivier; Fioretti, Florence; Tenenbaum, Henri; Georgel, Philippe; Wenzel, Wolfgang; Irusta, Silvia; Benkirane-Jessel, Nadia
Aim: We developed polymeric membranes for local administration of nonsoluble anti-inflammatory statin, as potential wound patch in rheumatic joint or periodontal lesions.Methods: Electrospun polycaprolactone membranes were fitted with polysaccharide-atorvastatin nanoreservoirs by using complexes with poly-aminocyclodextrin. Characterization methods are UV-Visible and X-ray photoelectron spectroscopy, molecular dynamics, scanning and transmission electron microscopy. In vitro, membranes were seeded with macrophages, and inflammatory cytokine expression were monitored.Results & conclusion: Stable inclusion complexes were formed in solution (1:1 stability constant 368 M - 1, -117.40 kJ mol - 1 ), with supramolecular globular organization (100 nm, substructure 30 nm). Nanoreservoir technology leads to homogeneous distribution of atorvastatin calcium trihydrate complexes in the membrane. Quantity embedded was estimated (70–90 μg in 30 μm × 6 mm membrane). Anti-inflammatory effect by cell contact-dependent release reached 60% inhibition for TNF-α and 80% for IL-6. The novelty resides in the double protection offered by the cyclodextrins as drug molecular chaperones, with further embedding into biodegradable nanoreservoirs. The strategy is versatile and can target other diseases.